2019
DOI: 10.1021/acscatal.9b01155
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Up Mechanistic Debris Generated by Twister Ribozymes Using Computational RNA Enzymology

Abstract: The catalytic properties of RNA have been a subject of fascination and intense research since their discovery over 30 years ago. Very recently, several classes of nucleolytic ribozymes have emerged and been characterized structurally. Among these, the twister ribozyme has been center-stage, and a topic of debate about its architecture and mechanism owing to conflicting interpretations of different crystal structures, and in some cases conflicting interpretations of the same functional data. In the present work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 103 publications
(240 reference statements)
4
49
1
Order By: Relevance
“…The active site shows how evolution has generated a perfect environment for catalysis of the transesterification, comprising in-line attack, transition state stabilization, and concerted general acid–base catalysis ( Figure 3). An alternative mechanism has been proposed for the twister ribozyme; for a neutral perspective on this, the reader is directed to an excellent critical evaluation by Breaker 39 and a very recent computational study 40 .…”
Section: G + A(n3): the Twister Ribozymementioning
confidence: 99%
“…The active site shows how evolution has generated a perfect environment for catalysis of the transesterification, comprising in-line attack, transition state stabilization, and concerted general acid–base catalysis ( Figure 3). An alternative mechanism has been proposed for the twister ribozyme; for a neutral perspective on this, the reader is directed to an excellent critical evaluation by Breaker 39 and a very recent computational study 40 .…”
Section: G + A(n3): the Twister Ribozymementioning
confidence: 99%
“…However, the field lacks a comprehensive understanding of the influence of solvated divalent cations on catalysis. Prior work on several self‐cleaving RNAs has shed light on the necessity of magnesium ions for maintaining structural integrity, as well as directly participating in catalysis . Recent structural and mechanistic work on pistol ribozymes highlights the unique paradigm of catalysis where a solvated divalent ion is crucial for involvement as a general acid .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests the Mg 2+ is specifically interacting with the RNA to stabilize the conformation of this region thereby facilitating formation of the T1 contact upon full folding of the RNA. Previous studies have reported conflicting results on the importance of this stem in folding and activity (34,37,38). Interestingly, Mg 2+ is not seen in this region of Twister in the crystallographic structures (34,38).…”
Section: Discussionmentioning
confidence: 89%
“…The Twister ribozyme was selected for the present study based on the availability of a range of structural and biochemical data (33)(34)(35)(36)(37)(38). While Twister sequences are extremely widespread, the crystal structure (PDB 4OJI) of the ribozyme used in this study is based on Osa-1-4 sequence from Oryza Sativa (34).…”
Section: Introductionmentioning
confidence: 99%